Identification with excess heterogeneity - Andrew Chesher (Centre for Microdata Methods and Practice (cemmap), 2005)
An outcome is determined by a structural function in which the effect of variables of interest is transmitted through a scalar function of those variables - an index. Multiple sources of stochastic variation are permitted to appear as arguments of the structural function, but not as arguments of the index. Conditions are provided under which there is local identification of ratios of partial derivatives of the index.
Keywords: 330; Zustandsraummodell; Statistischer Fehler